Innovation Knowledge Management Systems for Enhancing Education Quality Assurance at Rajamangala University of Technology Suvarnabhumi - Mahamad, Narissara; Phipataeksakul, Sompong; Suksai, Samphan; Singsoopa, Thawatchai; Sommit, Varothai (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The ever-changing landscape of higher education worldwide has led academic institutions to seek innovative strategies for ensuring globally competitive standards of excellence remain firmly in place. Knowledge management has increasingly come to the fore as a pivotal process supporting the ongoing refinement of educational quality at its core. Nevertheless, challenges persist in Rajamangala University of Technology Suvarnabhumi in systematically harnessing the power of knowledge into existing quality assurance mechanisms. This research aims threefold: first, to evaluate the current state and constraints of the university’s knowledge management application to quality assurance; second, to examine priority needs and defining success factors for crafting a customized knowledge management solution serving educational quality assurance; and third, to conceptualize and prototype an adaptive knowledge management system adequately responding to Rajamangala University of Technology Suvarnabhumi’s unique context and institutional imperatives. Materials and Methods: This mixed-methods study employed stratified random sampling to collect quantitative data from 276 university personnel. A five-point Likert scale questionnaire measured current Knowledge Management System (KMS) use and needs, demonstrating high reliability at 0.92. Descriptive statistics revealed frequency, percentage, means, and standard deviations of responses. Inferential statistics, including t-tests and one-way ANOVAs, identified significant differences at the 0.05 level. Six qualitative in-depth interviews with quality assurance administrators provided deep insights. Additionally, twelve quality assurance staff engaged in focus group discussions. Thematic analysis uncovered key themes within the qualitative data. Ultimately, findings informed the development of an innovative KMS using design thinking merged with the PDCA cycle. Fifteen quality assurance and IT experts then evaluated the effectiveness of the developed innovation. Results: The study into the university’s approach to knowledge management for quality assurance yielded intriguing findings. Firstly, the existing system was rated highly overall, with senior leadership endorsement seen as particularly strong. However, information technology use scored lower, highlighting a key area for improvement. A close examination pinpointed clear guidelines and administrators’ commitment as chief strengths, while segmented data and the lack of an integrated digital solution posed major obstacles. Staff highlighted the pressing need for a unified, user-friendly technological framework to consolidate disparate sources of information, reduce duplicate data entry, support insightful analytics, and facilitate online exchange of expertise. To address this, an innovative five-pronged quality assurance knowledge management system was developed, centered on the continual Plan-Do-Check-Act cycle. At its core were an integrated database, advanced applications, core functionalities, evaluation mechanisms, and a learning community. The system proved highly effective overall, earning especially high marks for its impact. Conclusion: The university had created an impressive system to organize its knowledge base that noticeably reduced duplicated efforts. It allowed staff to analyze information more thoroughly than ever before, gleaning valuable insights that impacted decision-making across divisions. Both junior and senior employees felt included in important discussions, sharing perspectives on how to strengthen the institution. This model shows great promise for other colleges in Thailand dealing with similarly intricate bureaucracies. With refinement, it could serve as an exemplar for rethinking how all members of a school - from freshman to dean - work together to continuously refine curriculum and operations. Its approach of pooling collective intelligence in a structured yet flexible manner may encourage lifelong dedication to scholarship within a community.